ANALISIS PENGUKURAN KONSENTRASI KARBONMONOKSIDA (CO) PADA BREATHING ZONE PETUGAS PARKIR BASEMENT MALL KOTA BANDUNG - Gede H Cahyana (ENVIROSAN : Jurnal Teknik Lingkungan, 2019)
Indoor air pollution in a closed room is one of the air pollutions that gives serious threats to human health. One of them comes from vehicle gas emissions in the closed parking area. This research identifies and analyses CO concentration measured in Mall X parking man’s breathing zone with closed parking area and in Mall Y semi-opened parking area. CO measurement carried out by passive sampling method using Personal Dosimeter Tubes. The measurement result of CO gas concentration to parking man’s breathing zone in Mall X was 25 – 81,25 ppm with the average value in 50 ± 26,15 ppm. Meanwhile, CO gas concentration in Mall Y gave result 3,13 – 12,5 ppm with the average value in 7,88 ± 4,36 ppm. Correlation value between CO concentration and its intake in Mall X area was 0,9983, meanwhile correlation value between CO concentration and its intake in Mall Y area was 0,9903. It was concluded that CO gas concentration measured in parking man’s breathing zone influenced the differences in CO intake value in significance value. Keywords: carbon monoxide, indoor air pollution, passive sampling, vehicle emission